Maklumat Program Siswazah (Mps): The Digitization Of Postgraduate Programs Information For The Centre For Graduate Studies (Cgs) - Jamuna Ranee, Jelani (Universiti Malaysia Sarawak, (UNIMAS), 2023)
The Centre for Graduate Studies (CGS) at UNIMAS plays a vital role in coordinating and developing Doctor of Philosophy and Master's Degree programs while upholding their quality standards in line with regulations set forth by the Ministry of Education and the Malaysian Qualifications Agency (MQA). Currently, manual filing systems are utilized, resulting in timeconsuming and inefficient processes. To address this issue, CGS has commissioned the development of a digitization system named 'Maklumat Program Siswazah' (MPS). This system aims to efficiently store and present postgraduate program information in a structured and tabular format. MPS encompasses essential features such as data creation, reading, updating, and deletion, alongside a quick filter search function for time-saving convenience. The system's development follows the Rapid Application Development (RAD) methodology, and hardware and software requirements are meticulously outlined, while data flow diagrams and wireframes illustrate the user design. To enhance the system, it involves resolving file updating limitations, optimizing system navigation, and providing training for administrators to improve functionality and usability. As a result, the implementation of the MPS system has led to significant achievements, including thorough documentation of system requirements and functionalities, a user-friendly interface for efficient program management and viewing, as well as a robust system ensuring organized categorization and display of correspondence.